2012
DOI: 10.1063/1.4768475
|View full text |Cite
|
Sign up to set email alerts
|

Optical absorption modulation by selective codoping of SiGe core-shell nanowires

Abstract: First-principles calculations on the structural, electronic, and optical properties of B-P codoped SiGe core-shell nanowires are discussed. We show that the simultaneous addition of B and P impurities into the wire can be energetically favored with respect to the single-doping. We demonstrate that impurities energetic levels in the band gap are dependent by the Si/Ge band offset, as well as by their location in the wire (i.e., core or shell region). This electronic tunability results in a significant optical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…These results were confirmed by the experimental determination of strong PL intensities in colloidal and matrix-embedded codoped Si-NCs [117]. Similar theoretical outcomes have been obtained also for codoped Si-NWs [236,237,243,244].…”
Section: Codopingsupporting
confidence: 83%
See 1 more Smart Citation
“…These results were confirmed by the experimental determination of strong PL intensities in colloidal and matrix-embedded codoped Si-NCs [117]. Similar theoretical outcomes have been obtained also for codoped Si-NWs [236,237,243,244].…”
Section: Codopingsupporting
confidence: 83%
“…6.1. Ab-initio calculations: codoped free-standing and matrix-embedded nanocrystals In order to interpret experimental results, we will report the outcomes of ab-initio simulations for B and P simultaneously codoped Si-NCs [65,82,92,145,146,147,166,177,232,233,234,235,236,237].…”
Section: Codopingmentioning
confidence: 99%
“…The analysis shows that the simultaneous addition of B and P impurities in Ge core /Si shell NWs can result in a gain of energy with respect to the single‐doping cases, as already demonstrated in the case of co‐doped Si NCs . The DFT calculations performed to investigate the electronic structure of such co‐doped systems revealed that the simultaneous presence of B and P impurities can induce a modification in both the band structure and electronic transitions if compared to pristine NWs . In particular, for co‐doped Si and Ge NWs, we found that: i) contrary to the behavior observed for co‐doped NCs, the impurity states only rather modify the band gap with respect to the undoped wire and ii) this reduction is influenced by the relative positions of dopants (if both in the core, both in edge or in the configuration core‐edge) as well as the distance between impurities.…”
Section: Si/ge Core–shell Nws: Dopingsupporting
confidence: 61%
“…This effect has negative consequences on the efficiency of the doping process because dopants in the surface interact with surface states becoming recombination centers for electrons and holes (thus reducing the carrier concentration). As for Si/Ge core–shell NWs, results of DFT formation energy are reported in Figure . The analysis shows that the simultaneous addition of B and P impurities in Ge core /Si shell NWs can result in a gain of energy with respect to the single‐doping cases, as already demonstrated in the case of co‐doped Si NCs .…”
Section: Si/ge Core–shell Nws: Dopingmentioning
confidence: 99%
“…The co‐doped Si‐NCs exhibit PL energies red‐shifted with respect to those of the corresponding undoped Si‐NCs, moreover these energies can range from the visible to below the bandgap energy of the bulk Si . Thus, we will report here the outcomes of a systematic study of the structural, electronic and optical properties of B and P simultaneously doped Si‐NCs using ab initio DFT calculations . Starting from the hydrogenated Si‐NCs we have co‐doped the Si‐NCs by locating the B and P impurities in all the possible substitutional positions allowing full relaxation with respect to all the atomic positions.…”
Section: Co‐dopingmentioning
confidence: 99%